MEDIATION ROLE OF AUDIT GOING CONCERN OPINION ON CORRELATION OF AUDIT TENURE AND MARKET PERFORMANCE - Annisa Rahmawati; Arsono Laksmana; Dian Agustia (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to obtain empirical evidence of the mediating role of going concern opinion audit on the relationship of audit tenure with company market performance. This research is explanatory. The subjects in this study were companies listed on the Indonesia Stock Exchange from 2007 to 2017. The samples in this study were 245 companies. The type of data used is quantitative data. The statistical analysis method uses path analysis with SPSS 13. The results of the study show that going concern audit opinion has a significant negative relationship in mediating audit tenure and company market performance. These results indicate that going concern audit opinion has information that is useful for users' financial data to make financial decisions.Keywords: Audit Tenure, Going Concern Audit Opinion, Market Performance